Examining Velopharyngeal Closure Patterns Based on Anatomic Variables. Issue 1 (January 2017) - Jordan, Holly Nelson; Schenck, Graham C.; Ellis, Charles; Rangarathnam, Balaji; Fang, Xiangming; Perry, Jamie L.
Abstract : Abstract: The purpose of this study was to use three-dimensional magnetic resonance imaging to correlate velopharyngeal closure patterns with velopharyngeal anatomic structural characteristics. Thirty-eight participants (18 females and 20 males) between 19 and 32 years of age participated in the study. Participants were evaluated using magnetic resonance imaging and nasopharyngoscopy to determine closure pattern type and their relationship to anatomic characteristics believed to influence velopharyngeal closure. Structural anatomic measures were completed in the vertical (nasopharyngeal length) and horizontal (nasopharyngeal width) planes. Anterior to posterior dimensions of pharyngeal depth, posterior pharyngeal wall thickness, velar length, effective velar length, and adenoid thickness were also completed. Velar length and adenoid thickness varied based on closure patterns, with coronal closure pattern demonstrating significantly larger values than circular closure pattern. There were no statistically significant differences for effective velar length, pharyngeal depth, nasopharyngeal length, posterior pharyngeal wall thickness, and nasopharyngeal width based on the type of closure pattern. Closure patterns varied by sex, with females demonstrating more circular closure patterns than males who demonstrated more coronal closure patterns. Nasopharyngeal length, velar length, and nasopharyngeal width also varied by sex, with males demonstrating significantly larger values than females. Statistically significant differences were observed in velopharyngeal anatomic structural measures and sex during evaluations of closure patterns. These preliminary findings indicate that the length of the velum and thickness of the adenoids may have the greatest impact on velopharyngeal closure patterns.